Measuring Higher Education Access: Purpose and Context - Malish, C. (International Higher Education, 2021)
Gross enrollment ratio (GER) is a widely used indicator to measure access to education. Recently, another indicator called eligible enrollment ratio (EER) was introduced. This article attempts to compare GER and EER and their utility in assessing the progress of higher education in India. This article argues that GER is more likely to remain the most appropriate indicator for measuring access to higher education.